Chemical characterization, antioxidant capacity and antimicrobial activity against food related microorganisms of Citrus limon var. pompia leaf essential oil. (June 2016) - Fancello, Francesco; Petretto, Giacomo Luigi; Zara, Severino; Sanna, Maria Lina; Addis, Roberta; Maldini, Mariateresa; Foddai, Marzia; Rourke, Jonathan P.; Chessa, Mario; Pintore, Giorgio
Abstract: In this study, leaves of Citrus limon var. pompia ( pompia ) were subjected to hydro-distillation and an essential oil (EO) was obtained. Gas chromatographic analysis allowed us to determine its chemical composition, both qualitatively and quantitatively: the major compounds in the EO were limonene, geranial and neral. In vitro DPPH and ABTS assays, conducted on the EO, demonstrate its ability to act as an antioxidant. The antimicrobial activity of the EO against 12 bacteria and 4 yeasts was tested by a microdilution broth test; in addition the effect on maximum growth rate (μ) and lag phase (λ) was assessed. Results show a low inhibitory activity against food grade and Lactobacillus strains, whereas Listeria monocytogenes and Staphylococcus aureus were inhibited at low EO concentration. The pompia EO demonstrated an antimicrobial activity against yeast, with Saccharomyces cerevisiae being the most sensitive strain. The pompia EO, even at sub-MIC concentration, negatively affects the microbial growth rate (μ) and delayed the lag phase on all pathogens microbial strains tested, except Candida albicans 3993. Highlights: Citrus limon var. pompia leaf essential oil exhibited a high antimicrobial activity. GC-FID method was validated for the analysis of essential oil. The main compounds of the essential oil were limonene, geranial and neral. Listeria monocytogenes and Staphylococcus aureus were inhibited at low concentration. Lactic acid bacteria were not inhibited by Citrus limon var. pompia essential oil.